Analisis persepsi dan implementasi pembelajaran berdiferensiasi guru biologi pada materi sistem ekskresi di SMA Negeri Kota Pematangsiantar: (An Analysis of Biology Teachers' Perceptions and Implementation of Differentiated Learning on the Topic of the Excretory System at State Senior High Schools in Pematangsiantar City) - Azzahra Ritonga, Viony; Hasruddin , Hasruddin (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2025)
This study aims to analyze the perception and implementation of differentiated instruction by biology teachers on the excretory system topic at public senior high schools (SMA Negeri) in Pematangsiantar City. A descriptive quantitative approach was employed, with data collected through questionnaires, observations, and interviews. The population consisted of all biology teachers teaching Grade XI, totaling 10 individuals. Sampling was conducted using a puposive sampling technique. The results showed that teachers’ perceptions of differentiated instruction were categorized as very good, with an average score of 87.4%. The implementation of differentiated instruction was also categorized as very good, based on two main indicators with average scores of 87.2% and 87.3%, respectively. These findings indicate that biology teachers in SMA Negeri Pematangsiantar have a strong understanding of differentiated instruction and are able to implement it effectively in the learning process. The implications of this study highlight the importance of ongoing support and professional development for teachers to maintain and enhance their differentiated teaching practices in order to accommodate students’ diverse learning needs. Abstrak. Penelitian ini dilatarbelakangi oleh pentingnya penerapan pembelajaran berdiferensiasi dalam upaya memenuhi kebutuhan belajar siswa yang beragam. Tujuan penelitian ini adalah untuk menganalisis persepsi dan implementasi pembelajaran berdiferensiasi oleh guru biologi pada materi sistem ekskresi di SMA Negeri Kota Pematangsiantar. Penelitian ini menggunakan pendekatan deskriptif kuantitatif dengan teknik pengumpulan data berupa angket, observasi, dan wawancara. Populasi penelitian meliputi seluruh guru biologi kelas XI yang berjumlah 10 orang, dengan teknik pengambilan sampel purposive sampling. Hasil penelitian menunjukkan bahwa persepsi guru terhadap pembelajaran berdiferensiasi berada dalam kategori sangat baik dengan rata-rata skor 87,4%. Implementasi pembelajaran berdiferensiasi juga tergolong sangat baik dengan dua indikator utama yang masing-masing memperoleh skor rata-rata 87,2% dan 87,3%. Kesimpulan dari penelitian ini menunjukkan bahwa guru biologi di SMA Negeri Kota Pematangsiantar memiliki pemahaman yang baik terhadap konsep pembelajaran berdiferensiasi dan mampu mengimplementasikannya secara efektif. Hasil ini menegaskan pentingnya pelatihan dan dukungan berkelanjutan bagi guru untuk mempertahankan serta meningkatkan praktik pembelajaran berdiferensiasi di kelas.